Development of a Fluorescent Reporter System to Delineate Cancer Stem Cells in Triple‐Negative Breast Cancer. (15th May 2015) - Thiagarajan, Praveena S.; Hitomi, Masahiro; Hale, James S.; Alvarado, Alvaro G.; Otvos, Balint; Sinyuk, Maksim; Stoltz, Kevin; Wiechert, Andrew; Mulkearns‐Hubert, Erin; Jarrar, Awad M.; Zheng, Qiao; Thomas, Dustin; et al.
Abstract: Advanced cancers display cellular heterogeneity driven by self‐renewing, tumorigenic cancer stem cells (CSCs). The use of cell lines to model CSCs is challenging due to the difficulty of identifying and isolating cell populations that possess differences in self‐renewal and tumor initiation. To overcome these barriers in triple‐negative breast cancer (TNBC), we developed a CSC system using a green fluorescent protein (GFP) reporter for the promoter of the well‐established pluripotency gene NANOG . NANOG‐GFP+ cells gave rise to both GFP+ and GFP − cells, and GFP+ cells possessed increased levels of the embryonic stem cell transcription factors NANOG, SOX2, and OCT4 and elevated self‐renewal and tumor initiation capacities. GFP+ cells also expressed mesenchymal markers and demonstrated increased invasion. Compared with the well‐established CSC markers CD24 − /CD44 +, CD49f, and aldehyde dehydrogenase (ALDH) activity, our NANOG‐GFP reporter system demonstrated increased enrichment for CSCs. To explore the utility of this system as a screening platform, we performed a flow cytometry screen that confirmed increased CSC marker expression in the GFP+ population and identified new cell surface markers elevated in TNBC CSCs, including junctional adhesion molecule‐A (JAM‐A). JAM‐A was highly expressed in GFP+ cells and patient‐derived xenograft ALDH+ CSCs compared with the GFP − and ALDH − cells, respectively. Depletion of JAM‐A compromised self‐renewal, whereas JAM‐A overexpression induced self‐renewal in GFP − cells. Our data indicate that we have defined and developed a robust system to monitor differences between CSCs and non‐CSCs in TNBC that can be used to identify CSC‐specific targets for the development of future therapeutic strategies. Stem Cells. Stem Cells 2015;33:2114–2125